2017
DOI: 10.26600/mollife.1.1.2.2017
|View full text |Cite
|
Sign up to set email alerts
|

Linking chromatin dynamics, cell fate plasticity, and tissue homeostasis in adult mouse hair follicle stem cells

Abstract: Cellular plasticity for fate acquisition is associated with distinct chromatin states, which include histone modifications, dynamic association of chromatin factors with the DNA, and global chromatin compaction and nuclear organization. While embryonic stem cell (ESC) plasticity in vitro and its link with chromatin states have been characterized in depth, little is known about tissue stem cell plasticity in vivo, during adult tissue homeostasis. Recently, we reported a distinct globally low level of histone H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In our recent studies, global reduction of H3 K4/9/27me3 (global hypomethylation) has been shown to occur in quiescent late catagen HFSCs compared to proliferative early anagen HFSCs, suggesting increased HFSC cell plasticity during quiescence, prior to HFSC fate decision for self‐renewal or differentiation 26,128 . Follow‐up in vitro and in vivo experiments further strengthened our model, where quiescent HFSCs were found to have higher chromatin factor exchange rates and increased tendencies to reprogram upon Yamanaka factors exposure, compared to their proliferative counterparts 128 . Data suggest that BMP signalling may be found both upstream and downstream of histone methylation in a negative feedback loop that remains to be directly tested in vivo 26,59 .…”
Section: Epigenetic Modifications and Chromatin Structuresupporting
confidence: 58%
See 2 more Smart Citations
“…In our recent studies, global reduction of H3 K4/9/27me3 (global hypomethylation) has been shown to occur in quiescent late catagen HFSCs compared to proliferative early anagen HFSCs, suggesting increased HFSC cell plasticity during quiescence, prior to HFSC fate decision for self‐renewal or differentiation 26,128 . Follow‐up in vitro and in vivo experiments further strengthened our model, where quiescent HFSCs were found to have higher chromatin factor exchange rates and increased tendencies to reprogram upon Yamanaka factors exposure, compared to their proliferative counterparts 128 . Data suggest that BMP signalling may be found both upstream and downstream of histone methylation in a negative feedback loop that remains to be directly tested in vivo 26,59 .…”
Section: Epigenetic Modifications and Chromatin Structuresupporting
confidence: 58%
“…26,128 Follow-up in vitro and in vivo experiments further strengthened our model, where quiescent HFSCs were found to have higher chromatin factor exchange rates and increased tendencies to reprogram upon Yamanaka factors exposure, compared to their proliferative counterparts. 128 Data suggest that BMP signalling may be found both upstream and downstream of histone methylation in a negative feedback loop that remains to be directly tested in vivo. 26,59 Results of our studies demonstrate the importance of histone methylation marks in adult HFSC function and suggest a link with quiescence and fate plasticity during homeostasis and injury repair.…”
Section: Epi G Ene Ti C Mod Ifi C Ati On S and Chromatin S Truc Turementioning
confidence: 56%
See 1 more Smart Citation
“…Similar with embryonic SCs, the catagen hypomethylation of HFSCs might allow high plasticity, or flexibility in subsequent SC fate acquisition (Figure 1A). In fact, we found that other measurements of plasticity, such as dynamic exchange of chromatin-bound factors, and reprogramming ability by the Yamanaka 4F factors are also elevated at Catagen (Lee and Tumbar, 2017).…”
Section: Introductionmentioning
confidence: 77%